HARNESSING NATURE'S POTENTIAL: BRANDING PENGLIPURAN BAMBOO FOREST AS AN ECOTOURISM DESTINATION IN BALI - Nofiasari, Wida; Seli, Fenny Yutika; Damayanti, Novita (Graduate Program of Universitas Tarumanagara, 2025)
The Penglipuran Traditional Village in Bali has a bamboo forest of approximately 45 hectares that is managed through the customary system (awig-awig), serving as a source of economic, ecological, and spiritual value for the community. This study aims to analyze the utilization of the natural power of the bamboo forest as an agent of change while shaping a new branding of ecological tourism in Bali. The research method uses a descriptive qualitative approach, with primary data collected through observation, documentation, and in-depth interviews, as well as secondary data from literature, articles, and relevant journals. The results show that the management of the bamboo forest through local wisdom creates a unique tourism identity, integrating ecological, socio-cultural, and economic aspects, while strengthening the community’s role as the main actor in environmental preservation. The bamboo forest becomes an educational tourism attraction through activities such as trekking, bamboo handicraft workshops, and participation in traditional ceremonies, while also maintaining ecosystem balance, disaster mitigation, and groundwater conservation. This new branding emphasizes authenticity and sustainability, making Penglipuran a model of ecological tourism capable of attracting both domestic and international tourists. In conclusion, the new branding of Penglipuran Bamboo Forest emphasizes the integration of nature conservation, cultural preservation, environmental education, and local economic empowerment through the utilization of bamboo in traditions, crafts, creative industries, and a bamboo laboratory, thereby positioning Penglipuran as a sustainable ecotourism destination that is authentic, educational, and globally valuable.